Baseline Demographics, Comorbidities, Treatment Patterns and Burden of Atopic Dermatitis in Adults and Adolescents from the GLOBOSTAD Long-Term Observational Study - Calzavara-Pinton, Piergiacomo; Čelakovská, Jarmila; Lapeere, Hilde; Holzer, Gregor; Al-Ahmad, Mona; Chu, Chia-Yu; Ferrucci, Silvia M; Kataoka, Yoko; Rossi, Mariateresa; Fomina, Daria S; Chung, Wen-Hung; Tzellos, Thrasyvoulos; et al. (Advances in therapy, 2023)
INTRODUCTION: Insights into real-world treatment of atopic dermatitis (AD) are relevant to clinical decision making. The aim of this analysis was to characterize patients who receive dupilumab for AD in a real-world setting. METHODS: The GLOBOSTAD registry is an ongoing, longitudinal, prospective, observational study of patients with AD who receive dupilumab according to country-specific prescribing information. We report baseline characteristics, comorbidities and treatment patterns for patients enrolled from July 11, 2019 to March 31, 2022. Analyses are descriptive; no formal statistical comparisons were performed. RESULTS: Nine hundred fifty-two adults and adolescents were enrolled in GLOBOSTAD. Patients had a high disease burden before starting dupilumab: (mean [standard deviation]) percent body surface area affected (44.8 [24.42]), Eczema Area and Severity Index total score (24.8 [12.95]), SCORing Atopic Dermatitis total score (60.5 [16.34]), Patient-Oriented Eczema Measure total score (19.7 [6.37]) and Dermatology Life Quality Index total score (13.7 [7.02]). Overall, 741 (77.8%) patients reported ≥ 1 type 2 inflammatory comorbidities, most frequently allergic rhinitis (492 [51.7%]), asthma (323 [33.9%]), food allergy (294 [30.9%]) or another allergy (274 [28.8%]). In the previous 12 months, 310 (32.6%) patients had received systemic non-steroidal immunosuppressants and 169 (17.8%) systemic corticosteroids; 449 (47.2%) had received topical corticosteroids, most commonly potent topical corticosteroids; 141 (14.8%) had received topical calcineurin inhibitors and 32 (3.4%) ultraviolet therapy. Most (713 [74.9%]) patients started dupilumab because of prior treatment failure. CONCLUSION: Patients enrolled in GLOBOSTAD demonstrated considerable multidimensional burden of disease across AD signs, symptoms and quality of life despite previous use of systemic and non-systemic AD treatments. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov identifier NCT03992417. Video Abstract.
Keywords: dospělí; Dermatitis, Atopic; Adult; výsledek terapie; Adolescent; kvalita života; lidé; dvojitá slepá metoda; Treatment Outcome; atopická dermatitida; Adrenal Cortex Hormones; hormony kůry nadledvin; Eczema; stupeň závažnosti nemoci; prospektivní studie; Double-Blind Method; Prospective Studies; Severity of Illness Index; ekzém; Quality of Life; mladiství; Humans